Adaptable effectiveness of industrialised building (IBS) in construction projects - Zulkarnain, Muhamad (2013)
Generally, implementation of Industrialized Building System (IBS) as a new technology has been proposed to be used in construction project. Used of IBS can reduce labor usage, increase productivity and better the quality of building construction. Unfortunately, construction using Industrialized Building System (IBS) are still lacking in Malaysia. This study is mainly focused on the effectiveness of IBS from perspective of respondents involved in construction projects who have had experienced using IBS and problems faced by people involved in construction projects who have experienced using conventional method. The data were collected through literature review and questionnaire through contractor within the Selangor district. From the findings, the level of IBS usage in construction projects is still low which is far from the government's target to fully implement the use of lBS in construction projects This study also found that the most effective IBS system in construction projects is reduce construction waste and produce a good and clean of construction site. The main problem faced by conventional method that can encourage IBS implementation in construction projects is dependence on foreign workers and poor quality of construction materials.